Sosialisasi Pemanfaatan Ilmu Geofisika Dalam Mitigasi Bencana Alam dan Pembangunan Kesadaran Lingkungan di Kalangan Pelajar SMP - Jusuf Leiwakabessy; Liora Chrissa Pattiasina (Jurnal Nusantara Berbakti, 2024)
One of the key topics in education and disaster mitigation is the use of geophysical science to deal with natural disasters and to raise environmental awareness of high school students. We discussed how geophysician science can be incorporated into high school curricula to increase environmental Awareness and reduce natural disaster risk. We also highlighted the methods of geofysics that can be socialized to high school pupils to understand and manage natural phenomena, as well as to reduce the risk of natural catastrophe for society. By using this method, high school children are expected to learn about the Earth and how to cope with natural catastrophes